2020
DOI: 10.7759/cureus.7927
|View full text |Cite
|
Sign up to set email alerts
|

Otosclerosis: Experience With Stapes Surgery

Abstract: Introduction Otosclerosis is a disorder in which the footplate of the stapes is replaced by an abnormal bone, thereby affecting sound transmission to the inner ear at the level of the oval window. The solution to this condition is to reestablish this mechanism back to normal via the ossicular chain to the inner ear. The aim of stapes surgery is to improve the hearing level to thresholds appropriate enough to obviate the need for hearing aid. The hearing improvement achieved after surgery often lasts for many y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In relation to sex, it was found a predominance of females, similar to what is widely described in the international literature 12 . In several studies consulted in our literature review, a decrease in ABG (GAP or air-bone space) to less than 10dB (decibels) is considered successful in stapes surgery [12][13][14] . In our evaluation, we observed that of the patients who did con-tinue with their postoperative follow-up with the Audiology service, approximately half of each group achieved this goal by having as a postoperative result an ABG less than 10dB.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to sex, it was found a predominance of females, similar to what is widely described in the international literature 12 . In several studies consulted in our literature review, a decrease in ABG (GAP or air-bone space) to less than 10dB (decibels) is considered successful in stapes surgery [12][13][14] . In our evaluation, we observed that of the patients who did con-tinue with their postoperative follow-up with the Audiology service, approximately half of each group achieved this goal by having as a postoperative result an ABG less than 10dB.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of the model, derived from the epidemiological analysis, are presented in Table 2 . 2 , 4 , 7 , 8 , 12 , 26 , 36 For the hearing aid group, costs were determined on a yearly basis, with a new device every 4 years ( Table 2 ). Based on audiologists’ estimates and sales figures provided by the Syndicat National de l’Industrie des Technologies Médicale, we assumed that 20% of patients using a hearing device would choose a class I device (the minimum target set by the state for audiologists in France), 35% would choose a class II, subgroup C or D device (class II), and 45% would choose a class II, subgroup E or F device (class III).…”
Section: Methodsmentioning
confidence: 99%
“…The parameters of the model, derived from the epidemiological analysis, are presented in Table 2 . For the hearing aid group, costs were determined on a yearly basis, with a new device every 4 years (Table 2).…”
Section: Methodsmentioning
confidence: 99%